Counsellor Role — Canadian Scene - Brown, Tom (Canadian Journal of Counselling and Psychotherapy, 2012)
A random sample of 220 CGCA members was surveyed, using a 44 Item Counsellor Role Questionnaire (CRQ), for present and preferred functions and responsibilities. Their clients and administrators were asked to respond to the CRQ in terms of how frequently CGCA members should perform each item. The most frequently reported activities of counsellor respondents were in the area of counselling clients with educational-vocational and personal-social psychological problems. Sixty per cent of counsellor respondents did not engage in group methods, consultation with other counsellors, public relations activities and research as often as they felt they should. Counsellors differed with their clients on twice as many CRQ items as they did with their administrators. Counsellors, clients, and administrators reached consensus on eight CRQ items, including counselling for educational-vocational and personal-social problems; confidential note-taking; consultation with other counsellors, community service agencies, and other helping professionals; and client follow-up.